Tarian Joged Bumbung: Diskursus Konsep Hukum Warisan Budaya Tak Benda - Satyawati, Ni Gusti Ayu Dyah (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 11 No 4 (2022), 2022)
Joged bumbung dance performances in Bali often lead to pornographic acts. This is regarded as an infringement of intangible cultural heritage. This article is outlined as a sociolegal study that aims to present an analysis of the joged bumbung phenomenon with reference to the legal concept of intangible cultural heritage, discusses the fulfillment of obligations and the role of the government, and discusses legal efforts to protect it through the imposition of legal sanctions. It suggested that the legal protection of intangible cultural heritage is contained in laws and regulations at the national level, including international legal instruments that have been ratified, and at the local level. The protection can be in the form of registration as well as other forms of protection carried out in accordance with norms, standards, procedures, and criteria in the field of culture which pay attention to aspects of religious values, traditions, values, norms, ethics, and customary law. Legal efforts to protect intangible cultural heritage in the form of the joged bumbung dance can be carried out by imposing customary, administrative, and/or criminal sanctions. However, there is a tendency for preventive efforts and supervision approaches in responding to the practice of joged bumbung. Pagelaran tarian Joged Bumbung di Bali kerap kali mengarah pada pornoaksi. Hal ini dipandang sebagai suatu pelecehan terhadap warisan budaya tak benda. Artikel ini disusun sebagai suatu penelitian sosiolegal yang bertujuan untukmenyajikan analisis fenomena joged bumbung dengan merujuk pada konsep hukum warisan budaya tak benda, membahas pemenuhan kewajiban dan peran pemerintah, serta mendiskusikan upaya hukum perlindungannya melalui pengenaan sanksi hukum. Hasil penelitian menunjukkan bahwa perlindungan hukum terhadap warisan budaya tak benda tertuang di dalam peraturan perundang-undangan di tingkat nasional, termasuk instrumen hukum internasional yang telah diratifikasi, dan di tingkat daerah. Bentuk perlindungan dapat berupa pendaftaran serta bentuk perlindungan lain yang dilaksanakan sesuai norma, standar, prosedur, dan kriteria bidang kebudayaan yang memperhatikan aspek nilai agama, tradisi, nilai, norma, etika, dan hukum adat. Upaya hukum melindungi  warisan budaya tak benda berupa tarian joged bumbung dapat dilakukan dengan menerapkan sanksi adat, sanksi, administrasi, dan/atau sanksi pidana. Hanya saja, terdapat kecenderungan upaya preventif dan pendekatan yang bersifat pembinaan dalam merespon praktik joged bumbung.